CoFe Nanoparticles in Carbon Nanofibers as an Electrode for Ultra-Stable Supercapacitor - Kurtan, U.; Sahinturk, U.; Aydin, H.; Dursun, D.; Baykal, A. (SPRINGER, 2020)
In this paper, we proposed the synthesis of CoFe nanoparticles (NPs) which have been deposited on carbon nanofibers (CNFs) with a facile electrospinning route followed by thermal reduction. The performance of obtained CNF supercapacitors are improved from 51 to 190 F/g (247 mF/cm(2)) at 0.5 A/g with the combination of CoFe NPs and graphitized carbon layers The device possessed an energy and power density of 6.6 Wh/kg and 125 W/kg, respectively. Furthermore, the capacitance retention can still maintain about 96.6% after 10,000 cycle test and it is worth noting that the cycling stability is ultrahigh. This research proves that bimetallic nanoparticles embedded in CNFs can elucidate new insights into the development new nanofiber electrode materials for the next generation of symmetric supercapacitors.
Keywords: Electrospinning; Carbon nanofibers; CoFe nanoparticles; Energy storage; Supercapacitors; HIERARCHICAL POROUS CARBON; MESO-MICROPOROUS STRUCTURE; PERFORMANCE; OXIDE; CAPACITANCE; COMPOSITES; NANOTUBES; Polymer Science